Guidelines in the management of diabetic nerve pain: clinical utility of pregabalin - Vinik, Aaron I (Dove Medical Press, 2013)
Diabetic peripheral neuropathy is a common complication of diabetes. It presents as a variety of syndromes for which there is no universally accepted unique classification. Sensorimotor polyneuropathy is the most common type, affecting about 30% of diabetic patients in hospital care and 25% of those in the community. Pain is the reason for 40% of patient visits in a primary care setting, and about 20% of these have had pain for greater than 6 months. Chronic pain may be nociceptive, which occurs as a result of disease or damage to tissue with no abnormality in the nervous system. In contrast, neuropathic pain is defined as “pain arising as a direct consequence of a lesion or disease affecting the somatosensory system.” Persistent neuropathic pain interferes significantly with quality of life, impairing sleep and recreation; it also significantly impacts emotional well-being, and is associated with depression, anxiety, and noncompliance with treatment. Painful diabetic peripheral neuropathy is a difficult-to-manage clinical problem, and patients with this condition are more apt to seek medical attention than those with other types of diabetic neuropathy. Early recognition of psychological problems is critical to the management of pain, and physicians need to go beyond the management of pain per se if they are to achieve success. This evidence-based review of the assessment of the patient with pain in diabetes addresses the state-of-the-art management of pain, recognizing all the conditions that produce pain in diabetes and the evidence in support of a variety of treatments currently available. A search of the full Medline database for the last 10 years was conducted in August 2012 using the terms painful diabetic peripheral neuropathy, painful diabetic peripheral polyneuropathy, painful diabetic neuropathy and pain in diabetes. In addition, recent reviews addressing this issue were adopted as necessary. In particular, reports from the American Academy of Neurology and the Toronto Consensus Panel on Diabetic Neuropathy were included. Unfortunately, the results of evidence-based studies do not necessarily take into account the presence of comorbidities, the cost of treatment, or the role of third-party payers in decision-making. Thus, this review attempts to give a more balanced view of the management of pain in the diabetic patient with neuropathy and in particular the role of pregabalin.